2021
DOI: 10.29121/ijoest.v5.i3.2021.193
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Strategic Leadership on Organisational Ambidexterity at the King Abdullah Ii Design and Development Bureau (Kaddb)

Abstract: This study aimed at identifying the impact of strategic leadership dimensions, such as defining strategic direction, investing strategic capabilities, and implementing balanced organisational supervision, on the organisational ambidexterity dimension at the King Abdullah II Design and Development Bureau (KADDB). The sample consisted of the directors at top and middle management at KADDB, totalling 92 directors. Further, a questionnaire was used as a tool for data collection through Google Forms for the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In a Jordanian study, Alshaer (2020) observed the impact of strategic vigilance on organisational ambidexterity in Jordanian Commercial Banks and found a positive effect of strategic vigilance on organisational ambidexterity. In another Jordanian study, Alzawahrah and Alkhaffaf (2021) studied the impact of strategic leadership dimensions on the organisational ambidexterity dimension at the King Abdullah II Design and Development Bureau (KADDB). The results of the questionnaire analysis revealed that there is a significant impact of strategic leadership approved on organisational ambidexterity at KADDB.…”
Section: Literature Review and Theoretical Framingmentioning
confidence: 99%
“…In a Jordanian study, Alshaer (2020) observed the impact of strategic vigilance on organisational ambidexterity in Jordanian Commercial Banks and found a positive effect of strategic vigilance on organisational ambidexterity. In another Jordanian study, Alzawahrah and Alkhaffaf (2021) studied the impact of strategic leadership dimensions on the organisational ambidexterity dimension at the King Abdullah II Design and Development Bureau (KADDB). The results of the questionnaire analysis revealed that there is a significant impact of strategic leadership approved on organisational ambidexterity at KADDB.…”
Section: Literature Review and Theoretical Framingmentioning
confidence: 99%
“…OA complements PL by providing a framework for exploring new sustainability initiatives while exploiting existing capabilities for efficiency and sustainable performance (Gibson and Birkinshaw, 2004). Burawat (2019) claimed that CSP demands resource efficacy, carbon footprint minimisation, green promotion and stakeholder amalgamation through adopting PL (Alzawahrah and Alkhaffaf, 2021). OA enables firms to translate paradoxical leaders' innovative ideas into action by providing the structures and processes needed to simultaneously explore and exploit for sustainable performance gains (O'Reilly and Tushman, 2013).…”
Section: Paradoxical Leadership and Corporate Sustainable Performancementioning
confidence: 99%
“…PL styles may have a synergistic effect on fostering the overall effect of the organisation, including SP (Greco et al, 2021). Burawat (2019) stated that SP requires resource efficiency, carbon footprint reduction, boosting green practices and stakeholder integration with a strategic leadership approach (Alzawahrah and Alkhaffaf, 2021). OA is a proactive synergy of exploitation and exploration that can move SMEs toward sustainability (Shafique et al, 2021).…”
Section: Adoption Of Smart Technologies and Organisational Ambidexteritymentioning
confidence: 99%